Prime cost estimate for the purposes of controlling - Temelkova, Miglena (НТУ "ХПІ", 2009)
Strategic purposes of the organization of production in reference to profitabileness, productivity and liquidity require rapid and effective management of changes to it and adapt it to a dynamically changing environment. This is achieved by means of controlling mechanisms leading to exact, correct and adequate estimate of the prime cost in the manufacturing organization. Thus, production and financial parameters in the organization of binding global and comprehensive, and require profound research and analysis of prime cost as a key indicator in the reporting system of controlling.

Стратегічна система виробничої організації по відношенню рентабельності виробництва і ліквідності вимагають ефективного управління і зміни усередині неї і адаптації до середовища, що швидко змінюється. Це можна здійснити за допомогою механізмів контролінга, які ведуть точний розрахунок собівартості у виробничій організації. Таким чином, виробничі і фінансові параметри в організації вимагають глибокого дослідження і аналізу собівартості як ключових показників звітності системи контролінга.
Розрахунок собівартості для потреб контролінгу